The Consequences of the Mixed Marriage Law Reviewed from Law No. 16 of 2019 - Lukmanulhakim, Zaidan; Guntara, Deni; Abbas, Muhamad (Dinasti Research, 2025)
Marriages between Indonesian citizens and foreign nationals have become more prevalent in the context of globalization. This research examines the legal framework governing mixed marriages under Law Number 1 of 1974 on Marriage and its amendment through Law Number 16 of 2019, alongside its connection to Law Number 12 of 2006 on Citizenship. Employing a normative juridical approach, the study analyzes the requirements for entering into mixed marriages, the procedures for their official registration, and the resulting legal implications for the spouses and their children. The study finds that a notable amendment in Law Number 16 of 2019 is the unification of the minimum marriage age to 19 years for both men and women, which has implications for the validity of mixed marriages when the foreign spouse’s national regulations differ. Additionally, proper marriage registration, whether within Indonesia or abroad, is essential to secure legal recognition and protect the rights of all parties involved. Children from mixed marriages are entitled to limited dual citizenship under Law Number 12 of 2006, valid until they turn 18 or marry, at which point they must choose one nationality. The study underscores the significance of legal certainty through marriage registration and the alignment of national, religious, and international laws to safeguard the rights of couples and their offspring.